Advanced Strategies for Overcoming Endosomal/Lysosomal Barrier in Nanodrug Delivery - Qiu, Chong; Xia, Fei; Zhang, Junzhe; Shi, Qiaoli; Meng, Yuqing; Wang, Chen; Pang, Huanhuan; Gu, Liwei; Xu, Chengchao; Guo, Qiuyan; Wang, Jigang (Research (Washington), 2023)
Nanocarriers have therapeutic potential to facilitate drug delivery, including biological agents, small-molecule drugs, and nucleic acids. However, their efficiency is limited by several factors; among which, endosomal/lysosomal degradation after endocytosis is the most important. This review summarizes advanced strategies for overcoming endosomal/lysosomal barriers to efficient nanodrug delivery based on the perspective of cellular uptake and intracellular transport mechanisms. These strategies include promoting endosomal/lysosomal escape, using non-endocytic methods of delivery to directly cross the cell membrane to evade endosomes/lysosomes and making a detour pathway to evade endosomes/lysosomes. On the basis of the findings of this review, we proposed several promising strategies for overcoming endosomal/lysosomal barriers through the smarter and more efficient design of nanodrug delivery systems for future clinical applications.